Emergency nurses' perceptions of the health care system and how it impacts provision of care to people who self-harm. Issue 1 (February 2022) - McGough, Shirley; Wynaden, Dianne; Ngune, Irene; Janerka, Carrie; Hasking, Penelope; Rees, Clare
Abstract: Background: Self-harm is a deliberate act to cause physical harm to oneself. People who self-harm are at greater risk for suicide than people who do not self-harm. Emergency nurses are first responders to many people who present to the emergency department (ED) with self-harm. The care they provide can influence future presentations to the emergency department and long-term outcomes. Aim: The aim was to explore ED nurses' experiences of working with people who self-harm. Methods: Semi-structured interviews were conducted with 18 emergency nurses from different locations in Australia in 2019. Elo and Kyngäs' inductive content analysis research method guided all stages of the research. Results: The category "health care system" emerged from the data. It comprised five subcategories: (i) Complexity of the work environment; (ii) ED staff attitudes and care provision; (iii) the mental health patient; (iv) facilitators and barriers to providing care to people who self-harm; and (v) lack of community resources. Discussion: This study found there were several factors influencing ED nurses' knowledge, skills and confidence in caring for people who self-harm and several factors influenced their experience. Conclusion: While participants felt confident to manage the physical injuries associated with self-harm, they were less confident to engage with the person about their self-harm. The article provides guidance for ED nurses to assess and intervene with people who present with self-harm.